Analysis Of GC Coffee Product Quality At Pt.X - Ardhyani, Ika Widya; Anshori, Moch; Yucha, Nikma; Adriansyah, Gusti; Alfian, Andi; Pramudita, Rezki Aulia (IQTISHADequity jurnal MANAJEMEN, 2023)
PT. X is a manufacturing company engaged in the processing of coffee beans. In line with its development, PT. X innovates in creating new products, one of which is GC coffee, which is a combination of creamer, coffee powder, milk powder, and sugar. In the production process, the company strives to always provide the best for consumers in terms of quality and price. The quality improvement method is the seven tools, which is a method to find out the root causes of problems. The tools used to analyze this research are flowcharts, check sheets, Pareto charts, control charts, histograms, distribution diagrams, and Root Cause Analysis (RCA). The results of the data analysis revealed that non-standard product types occurred for GC coffee products during January and June—total production from January to June: 2,372,411 sachets, Number of defects: 148,820 sachets. Three factors cause defects: taste mismatch: 7,120 sachets, inappropriate packaging: 73,323 sachets, improper weight: 68,377 sachets. Based on the results of calculations and analysis using the seven tools method and the 5 whys method, the most dominant defect is inappropriate packaging, so the proposed improvements are focused on these defects. The progress made is maintenance and continuous repair of machines with problems, complying with the SOP that has been set by the company correctly, and scheduling machine maintenance.